Cervical spondylotic radiculopathy: Early result from a conservative therapy - Zakaria@Mohamad, Zamzuri; See, Lei Peng (Juniper Publishers INC., 2019)
Introduction: Patients who had cervical spondylotic radiculopathy without major motor deficit and no evidence of cord compression will have good outcome with non-operative measures. The aim of this study was to determine the severity of degenerative changes on plain radiograph among the patients with cervical spondylotic radiculopathy, their rated outcomes following conservative treatment and to evaluate correlations between pain score with: 1) neck disability index, 2) severity of degenerative changes of the cervical spine and 3) different level of root compression. Methods: This is an observational cohort study recruiting all patients with a clinical diagnosis of cervical spondylotic radiculopathy treated conservatively between December 2016 and January 2018. One-way ANOVA, paired sample test, and Pearson’s correlation test were used for correlation analyses. The total of 29 patients was used to achieve the power of 80% at 0.05 significance level, in detecting a difference of five score from a mean of 28.6 with an estimated standard deviation of 9.2, using a two-sided one-sample t-test. Results: Neck disability index (NDI) and pain score showed significant correlation after conservative treatment (p<0.001). However, this was not observed between pain score and radiographic severity grade, or between pain score and different level of nerve root compression. Conclusion: Patients with cervical spondylotic radiculopathy treated conservatively showed favorable clinical outcomes. Keywords: Cervical spine; Conservative treatment; Degenerative spine; Radiculopathy